Characterization of Protected and Unprotected Ancient Glass after Acid Corrosion - Ana-Maria Mocioiu; Oana Cătălina Mocioiu (Proceedings, 2020)
In the last years, the interest to protect the integrity of historical objects has increased worldwide [...]